How are minimum wages set? - Richard Dickens (IZA World of Labor, 2023)
The minimum wage has become an accepted way to tackle the extremes of low pay in many countries, but there is considerable variability in the way minimum wages are set around the world. Methods include formulas, government rate setting, union bargained rates, and rates recommended by an expert body. Expert bodies whose recommendations are informed by a strong evidence base have the advantage that they can respond to changing economic conditions and build consensus among businesses and workers without political interference, but they are unlikely to take the sort of bolder steps seen in the UK, Germany and other countries in recent years.
Keywords: E24; J38; J88; 330; minimum wages; wage setting; expert body